Plant-derived utility products: knowledge comparison across gender, age and education from a tribal landscape of western Himalaya - Alpy Sharma; Deepika Thakur; Sanjay Kr. Uniyal (BMC, 2019)
Abstract Background Plant-derived utility products (PDPs) play an important role in sustaining humans, especially tribal communities. Despite this, knowledge on PDPs is declining. Methods The present study was therefore carried to document the PDPs used by Bhangalis, a tribal community of western Himalaya, through door-to-door surveys (n=420) and detailed questionnaire recordings (n=240). In addition to taxonomic richness, frequency of species used; use value (UV), use diversity (UD), and cultural importance index (CI) were also analysed. Knowledge comparison between genders, four identified age groups (group 1: 16-32 years, group 2: 33-49 years, group 3: 50-66 years, group 4: >66 years), and level of education of the respondents was also carried out using multiple regression in SPSS. Results Bhangalis reported 55 PDPs under five use categories namely tools (34), artefacts (7), construction and storage (6 each), and miscellaneous (2). For making these PDPs, 20 plant species representing 12 families were used. Picea smithiana (16.54%), Cedrus deodara (14.96%), Cotoneaster bacillaris (12.60%) and Quercus semecarpifolia (11.02%) reported the highest use frequency. On an average 15.13±0.25 PDPs per respondent was noted. Similarly, Picea smithiana (UV=0.088) and Cedrus deodara (UV= 0.079) reported the highest UV when compared to other species. Amongst all the species, maximum UD was revealed for Juglans regia in the tool category (0.91). On the other hand, maximum CI was also recorded for Picea smithiana (CITotal=2.91). With respect to gender, males were found to be more knowledgeable than females (B=6.370, p=0.001). Amongst the four age groups, respondents in group 1 (B=-13.302, p=0.001) and group 2 (B=-5.867, p=0.001) were less knowledgeable in comparison to respondents in the third and fourth age groups. Similarly, education also had a significant negative coefficient (B=-0.275, p=0.037), with educated respondents having lesser knowledge. It was observed that alternates available in the market seem to be limiting the use of PDPs. Conclusions Bhangalis still use PDPs that have a crucial role in their lifestyle. However, their use is declining. A multipronged strategy that not only focusses on socio-economic characteristics but also on awareness especially at school levels is desired.